DMBT1 is upregulated in lung epithelial cells after hypoxia and changes surfactant ultrastructure - Müller, Hanna; Schmiedl, Andreas; Weiss, Christel; Ai, Maria; Jung, Susan; Renner, Marcus (Pediatric Pulmonology, 2020)
Background: Hypoxia and asphyxia are known to induce surfactant inactivation in newborns. Deleted in Malignant Brain Tumors 1 (DMBT1) is an innate immunity protein with functions in epithelial differentiation and angiogenesis. It was detected in hyaline membranes of infants with respiratory distress syndrome. Human recombinant DMBT1 is able to increase the surface tension of exogenous surfactant preparations in a dose-dependent manner. Methods: Immunohistochemistry was performed on lung sections of infants who died due to pre-, peri- or postnatal hypoxia. The lung epithelial cell line A549 was stably transfected with a DMBT1 (DMBT1+ cells) expression plasmid or with an empty plasmid (DMBT1− cells). The cells were cultured in normoxic or hypoxic conditions, and then DMBT1 as well as HIF-1α RNA expression were analyzed by using real-time-polymerase chain reaction. Human recombinant DMBT1 was added to the modified porcine natural surfactant Curosurf to examine the effect of DMBT1 on surfactant ultrastructure with electron microscopy. Results: DMBT1 expression was upregulated in human lung tissue after fetal/peri-/postnatal hypoxia. In addition, in vitro experiments showed increased DMBT1 RNA expression in A549 cells after hypoxia. HIF-1α was upregulated in both DMBT1+ and DMBT1− cells in response to hypoxia. The addition of human recombinant DMBT1 to Curosurf caused an impaired surfactant ultrastructure. Conclusions: DMBT1 is upregulated in response to hypoxia and there seems to be a link between hypoxia and surfactant inactivation.
CRIS-Team Scopus Importer:2020-08-28
Keywords: DMBT1; hypoxia; lung epithelial cells; surfactant